Keterlibatan Masyarakat dalam Pemanfaatan Dana Desa di Negeri Batu Merah - Nandra Hana Zakhira Notanubun; Mohamad Arsad Rahawarin; Ivonny Yeany Rahanra (MAN 4 Kota Pekanbaru, 2026)
This study analyzes community involvement in the utilization of Village Funds in Negeri Batu Merah, Sirimau District, Ambon City. The study responds to a practical governance problem: although Village Funds have financed physical development and community empowerment programs, citizen involvement has not been evenly distributed across planning, implementation, monitoring, and evaluation. A qualitative descriptive method was used through interviews, observation, and documentation involving village officials and community representatives. The findings show that community involvement exists but remains uneven. Participation in planning is mainly consultative through village deliberation forums; involvement in implementation is relatively active through mutual-help activities; while monitoring and evaluation remain limited because access to information, socialization, and public awareness are not yet optimal. The study implies that Village Fund governance needs stronger transparency mechanisms, broader deliberative spaces, and community-based monitoring so that development priorities are more accountable and responsive to local needs.